A Multidimensional Evaluation of Intimacy. (1st August 2022) - Sears, M; Crosby, C; Freihart, B; McMahon, L; Meston, C
ABSTRACT: Introduction: Intimacy is crucial for developing successful relationships as it strengthens bonds between partners. Intimacy has been hypothesized to comprise four central components: self-disclosure, love and affection, validation, and trust. Despite the importance of intimacy in developing strong relationships, to our knowledge, there is not a widely accepted measure that captures the full spectrum of intimacy. Popular measures like the Miller Social Intimacy Scale (MSIS), the Personal Assessment of Intimacy in Relationships (PAIR), and the Fear of Intimacy Scale (FIS) each address only some facets of this multidimensional construct. As such, the development of a more inclusive relational intimacy scale would benefit both researchers and clinicians and help advance our understanding of this construct. Objective: The current study had two primary aims: (1) to identify what acts and experiences elicit feelings of intimacy among individuals in order to develop a more nuanced, complete measure for use in future research and clinical practice; and (2) to evaluate how the factor structure of these items compares to pre-existing measures of intimacy. Methods: In Study 1, participants nominated over 2, 700 items that "elicited feelings of intimacy" for them. Examples of nominations included: trust, communication, touch, attraction, and sex. Trained raters condensed duplicate items and created a final list of unique nominations for use in Study 2. Five experts in the field of sex research submitted additional items for consideration in Study 2 based on previous conceptualizations of this construct. Study 2 identified the factor structure of these items and validated the measure. Results: Data collection for Study 2 is ongoing, but will be completed in January 2021. Results will be updated with an addendum after data analysis. Conclusions: Discussion will focus on individual differences in the factor structure of intimacy based on gender, age, and relationship duration and status. We will conclude by positioning our new model of intimacy within the existing theoretical framework of this construct, and elucidate how our measure can improve psychological and clinical research. Disclosure: No